The determination of post-exposure regrowth effects and the bactericidal activity of selected antimycobacterial agents against mycobacterium tuberculosis - Masango, Refilwe Winstance (University of Limpopo, 2000)
Refer to document
Thesis (M.Sc. (Medical Sciences)) --University of Limpopo, 2000
Keywords: bactericidal activity; Antituberculosis drugs; Antimycobacterial agents; Mycobacterium tuberculosis -- South Africa.; Tuberculosis - Microbiology.